Correction: The diagnostic value of skin biopsies in Sneddon syndrome. - N L P Starmans; S Zoetemeyer; M R van Dijk; L J Kappelle; C J M Frijns (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0253365.].